Matemática na prática: uma proposta de formação continuada para professores dos anos iniciais do ensino fundamental - Zulianelo, Vagner (My University, 2022)
This study focuses on contributing to the improvement of the teaching practice of teachers who work in elementary school, from the perspective of continued training in Mathematics. The target audience of this research was teachers who have basic training in Primary Teaching and/or Graduation in Pedagogy and who work in classes from the Elementary Schools of the Municipal Education Network (RME in Portuguese) of Caxias do Sul. The instruments used to collect data were an initial diagnostic questionnaire, which served to outline, give shape and content to the course and to the activities to be developed, as well as the didactic plans produced, the activities promoted, participation in virtual learning games, collaborative digital wall, in addition to the questionnaire on the reading and also the written reports in a reflexive-critical-discursive way about the activities performed and the knowledge learnt. The analysis of data from the diagnostic questionnaire is represented using descriptive statistics and expressed in the form of a text with appropriate perceptions. The materials produced during the course, as long as the activities developed and the descriptive-reflective records, prepared at the end of meetings, were analyzed under the Textual Discursive Analysis (ATD in Portuguese). The theoretical support used in the research consists of the conceptions of Mathematics Education defended by Ubiratan D'Ambrósio, translated into the proposal of continuing training, especially characterized by Francisco Imbernón, and in the light of BNCC (BRASIL, 2017) and BNC-Training Continued (BRASIL, 2020). Based on the course developed, it was possible to conclude that the proposal implementation was possible through the culmination of some relevant factors: training planning based on the real needs identified within the target audience; adoption of different strategies and resources with easy access and handling; selection of practical and playful activities; engaged, dedicated and committed participants; and valuing their experiences and potentials. Furthermore, it is noteworthy that Mathematics Education played a relevant role in this result, as it allowed that participants saw mathematical knowledge from other angles, and it made the difference for them. [resumo fornecido pelo autor]
Este estudo tem por objetivo contribuir para o aprimoramento da prática docente de professores que atuam nos anos iniciais do Ensino Fundamental, na perspectiva da formação continuada em Matemática. O público-alvo da pesquisa foi constituído por professores que possuem formação inicial em Magistério e/ou Graduação em Pedagogia - Licenciatura e atuam em turmas dos anos iniciais do Ensino Fundamental da Rede Municipal de Ensino (RME) de Caxias do Sul. Os instrumentos utilizados para coleta de dados foram questionário diagnóstico inicial, que serviu para delinear, dar forma e conteúdo ao curso e às atividades a serem desenvolvidas, bem como os planejamentos didáticos produzidos, das atividades promovidas, da participação em jogos virtuais de aprendizagem, do mural digital colaborativo, além do questionário sobre leitura realizada e dos relatos escritos de forma reflexiva-crítica-discursiva sobre as atividades realizadas e as aprendizagens consolidadas. A análise dos dados provenientes do questionário diagnóstico aplicado é representada utilizando estatística descritiva e expressa na forma de texto com as devidas percepções. Os materiais produzidos no decorrer do curso, das atividades desenvolvidas e dos registros descritivo-reflexivos, elaborados ao final de cada encontro, são analisados à luz da Análise Textual Discursiva (ATD). O aporte teórico utilizado na pesquisa consiste nas concepções da Educação Matemática defendidas por Ubiratan D'Ambrósio, traduzidas na proposta de formação continuada, caracterizada especialmente por Francisco Imbernón, e à luz da BNCC (BRASIL, 2017) e da BNC-Formação Continuada (BRASIL, 2020). A partir do curso desenvolvido, concluiu- se que a concretização da proposta foi possível mediante a culminância de alguns fatores relevantes: planejamento da formação a partir das reais necessidades identificadas junto ao público-alvo; adoção de diferentes estratégias e recursos de fácil acesso e manuseio; seleção de atividades práticas e lúdicas; participantes engajados, dedicados e comprometidos; e valorização das suas experiências e potenciais. Além disso, ressalta-se que a Educação Matemática teve papel relevante nesse resultado, pois ela permitiu que as participantes enxergassem o conhecimento matemático a partir de outros ângulos, o que fez a diferença para elas. [resumo fornecido pelo autor]
Keywords: Professores - Formação; Educação permanente; Matemática (Ensino fundamental); Matemática - Estudo e ensino; Teachers, Training of; Continuing education; Mathematics (Elementary School); Mathematics - Study and teaching